International Experience in Assessing Economic Security: Basic Approaches and Opportunities for Ukraine - D. O. Koshikov (Law and Safety)
It has been stated that the implementation of state policy in the field of economic security of the country requires systematic monitoring and adjustment, taking into account the rapid changes in the global world and economic space. This monitoring of the state of economic security of the country should be carried out by obtaining and studying certain factual data that allows to make a conclusion about the effectiveness of joint efforts of the authorized state agencies in the direction of national economic security.